A systematic review and thematic synthesis on the experiences of accessing and attending psychological therapy for informal carers of people living with dementia - Jacquelyn Yang; Caroline Fearn; Amber John; Sarah Hoare; Seryn Chang; David Zammitt; Joshua Stott (BMC Geriatrics)
Abstract Background Informal carers of people living with dementia are at a higher risk of experiencing mental health difficulties than the general population, yet many are not able to access timely psychological support and their psychological needs are often overlooked. It is therefore important to develop a greater understanding of carers’ lived experiences in accessing and attending psychological therapy, to help tailor therapies to meet their individual needs. To our knowledge, this is the first thematic synthesis of qualitative literature on carers’ experiences of accessing and taking part in psychological therapies. Methods Three databases were systematically searched for qualitative literature, and 23 studies were included. Their quality was assessed and the data extracted was included in the thematic synthesis. Results Findings were organised into five overarching themes: i) Mental health and relationship difficulties (context); ii) Overall positive experiences of therapy (including specific techniques, therapist factors and therapeutic relationship, social support); iii) Common changes experienced (e.g. increased awareness of one’s emotions and needs, increased self-care and self-compassion); iv) Unhelpful experiences of therapy, suggestions and further needs; and v) Impact of wider societal contexts and events. Conclusions Given the predominantly positive experiences of therapy and mechanisms of change described, findings suggest that psychological therapies can be helpful for carers of people living with dementia. Additionally outlined are specific techniques to tailor therapy (regardless of approach) to best meet carers’ needs, and suggestions for improvement. Future research should try to understand for whom and under what circumstances (e.g. wider contexts) psychosocial interventions become most effective in this population.